2002
DOI: 10.5858/2002-126-0336-ciacbc
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Automated Complete Blood Cell Count and Differential Leukocyte Count Results Induced by Storage of Blood at Room Temperature

Abstract: Objective.—To delineate changes that occur in various parameters of automated complete blood cell count (CBC) and differential leukocyte count (differential) on prolonged storage of blood at room temperature. Design.—A CBC and an automated differential were performed on the Coulter Gen.S on 40 K3 (tripotassium ethylenediamine-tetraacetate) EDTA-anticoagulated blood specimens once daily, specimen volume permitting, for 3 to 7 days. Specimens were kept at room temperature throughout the study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 5 publications
2
11
0
2
Order By: Relevance
“…However, they did not observe the same increase in monocyte numbers. They concluded that these changes in the leukocyte sub-parameters could be due to cellular degeneration known as loss of individual cell properties and cell aging [9]. In our study, it supports Gulati et al 's findings.…”
Section: Discussionsupporting
confidence: 92%
“…However, they did not observe the same increase in monocyte numbers. They concluded that these changes in the leukocyte sub-parameters could be due to cellular degeneration known as loss of individual cell properties and cell aging [9]. In our study, it supports Gulati et al 's findings.…”
Section: Discussionsupporting
confidence: 92%
“…2 In human blood samples, the RBC count shows stability for up to 7 days. 19 However, RBC count stability may be species-related. Notably, the RBC count has been reported to change within 24 hours of sampling in dogs, 16 but remains consistent for 24 hours in rhesus macaques.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term storage of blood affects LDCs (Gulati et al, 2002). We therefore tested if the Epi-Blood-Count is also applicable after storage of blood samples for seven days at 4°C.…”
Section: Deconvolution Of Granulocytes Monocytes and Lymphocytes With Three Cpgsmentioning
confidence: 99%